Dinamika Bahasa Indonesia Terkait Tantangan Menjaga Kebakuan Bahasa pada Mahasiswa PPKn sebagai Generasi Z - Roma Nauli Stephany Bintang; Juni Kristiani Meiala; Faiz Muhammad Zacky; Otistas C. Sembiring; Nurul Azizah (Universitas 45 Surabaya, 2025)
This study examines the dynamics of the Indonesian language and the challenges in maintaining language standards among Pancasila and Citizenship Education (PPKn) students as Generation Z. Using a library study method, this study analyzes literature related to language standards, the development of the Indonesian language, and factors that influence its use among students. The discussion covers four main aspects. First, the understanding of language standards among PPKn students, including the definition and its application in an academic context. Second, the dynamics of the Indonesian language, which highlights the development of the language due to the influence of technology and social media. Third, the challenges in maintaining language standards, which are divided into two subtopics: the influence of social media that encourages the use of non-standard language, and the perception of standards that are often considered irrelevant by students. Finally, this study explores strategies to maintain language standards, such as effective language education and initiatives from educational institutions to increase student awareness. The results of the study are expected to be collaborative efforts between the government, educational institutions, and the community needed to increase awareness of the importance of using good and correct Indonesian and provide in-depth insight into the importance of maintaining language standards among PPKn students as generation Z, thus the identity and cultural heritage of the nation can be maintained amidst the flow of globalization and technological developments.